Hubungan School Well-Being dengan Motivasi Belajar Daring Selama Pandemik Covid-19 pada Mahasiswa Psikologi - Renjaan, Aphroditha Salsabilla (Universitas Muhammadiyah Metro, 2024)
The role of school well-being and learning motivation is one of the factors that become successful in applying online learning. This study aims to determine the relationship between school well-being and education. This research involved 325 students from the Faculty of Psychology at Makassar State University. This study used a simple random sampling technique to select population samples. The data obtained are analyzed using product moment analysis techniques. The study found a positive and significant relationship between school well-being and learning motivation. Other findings in the study showed that by gender, there was no significant difference in learning motivation score outcomes. There were significant differences in school well-being outcomes with a relatively strong correlation, so the higher the school well-being experienced by active students of the Faculty of Psychology, Makassar State University, the higher the learning motivation for students.